Integration of Venezuelan Refugees and Migrants in Brazil - Shamsuddin, Mrittika (World Bank, Washington, DC, 2021)
An unprecedented number of Venezuelans have left behind the worsening economic and social crisis at home to look for better future prospects. Brazil is hosting about 261,000 Venezuelans as migrants, asylum seekers, or refugees, which, at 18 percent, constitutes the largest share of Brazil’s 1.3 million refugees and migrants population (as of October 2020). Although previous literature on other host countries found that Venezuelan refugees and migrants are struggling to secure high-paying jobs that are commensurate with their education, little is known about their access to education and social protection. This paper fills this gap by analyzing various administrative and census data to explore whether Venezuelan migrants and refugees face differential access to education, the formal labor market and social protection programs. It finds that even though there is minimum legal constraints and work permits are relatively easy to obtain, Venezuelan refugees and migrants face challenges integrating into the education system, social protection programs and the formal labor market. The results suggest that Venezuelan refugees and migrants have faced downgrading in grades at school and occupations at work. They are more likely to attend overcrowded schools than their host community counterparts and more likely to do inferior jobs characterized by temporality, lower wages and higher hours worked. Overall, the results suggest that improvement in school capacity, accreditation of Venezuelan education or degrees and relocation to places with favorable employment opportunities may facilitate integration.